Zjawisko wypłat dywidend w przedsiębiorstwach rolniczych i w spółkach giełdowych sektora spożywczego - Franc-Dąbrowska, Justyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The article discusses payment of dividend in agricultural enterprises and stock companies in food sector. That compared groups of enterprises owned similar features in range of payment of dividend equal, as well as distinct differences took a stand. It regard investigative hypothesis as verified to part ultimately only positively.